The Effects of Hands-on Cadaver Dissection Module on Preclinical Students - Babacan, Serdar; Çitak, Devran; Deniz, Mustafa (European Journal of Therapeutics, 2024)
Objective: The anatomy education provided by cadaver dissection contributes to the professional skills of medical students. In addition to gaining scientific experiences, dissection practices contribute to the humane approach to the patient, motivation to become a physician, privacy, and ethical issues. Cadaver dissection is one of the oldest methods used in anatomy education, and the moment of encounter with the cadaver significantly affects medical students. The aim of the study was to emphasise the importance of traditional cadaver dissection and raise awareness about body donation. Methods: The study included 206 preclinical period students. After receiving the dissection materials, the students dissected cadavers, and the instructors helped them throughout the process. After the dissection, we shared an online survey. Results: 96.6% of the students emphasised that cadaver dissection is important and should be included in the curriculum. Also, 96.6% stated that the dissection module informed them about ethical values. 94.2% declared that dissection increased their interest and motivation towards medical education. 91.8% of the students thought that participation in cadaver dissection provided them with more opportunities to develop professional skills than the demonstration of a prosectioned (previously dissected) cadaver. 71.8 of them stated that the models or computer-assisted education can not replace cadaver dissection. Conclusion: However, although technology and artificial intelligence facilitate learning, the multifaceted benefits of the cadaver cannot be denied, and the cadaver cannot be excluded from anatomy education.